Large-scale cultural events: An argument for strengthening ecological awarenes - Iuliana Cetină; Silvia Elena Cristache; Georgeta Narcisa Ciobotar; Andrei Badin (Amfiteatru Economic Journal, 2020)
The economic-social and technological dynamism, the changes produced in the natural environment force the society to change the attitude and the behavior towards the environment by developing the ecological awareness, a process that must materialize in a behavior of acquisition, purchase and consumption based on ecological principles and criteria. The major differences in consumer behavior, business practices, and entrepreneurial practices are an effect of cultural differences. Under the conditions of sustainable and systematic development of the states of the world, it has become necessary to consider cultural institutions as organizations that through their purchasing behavior based on ecological principles and by creating and transmitting thematic messages, can significantly contribute to the development of the ecological awareness of the society. In this context, the purpose of the research is to determine the impact of major cultural events on increasing the awareness of the society regarding the protection of the environment, through the component of ecological acquisitions. The opinion poll conducted took into account the participants' perceptions during large-scale cultural events regarding the importance attributed by organizers to the development of the ecological awareness and the way in which they practice ecological acquisitions. Also, through this survey it was aimed to establish the existence or non-existence of the relationship between the degree of reception of the message with ecological theme of the organizers and the demographic-cultural characteristics of the attending public, implicitly of the society. The aim was to analyze the need of increasing major cultural events organizers' degree of involvement in increasing participants' ecological awareness by diversifying the types of actions that will stimulate acquisition, buying and ecological consumption behavior.
Keywords: M30; Q01; M31; Q57; 330; development of ecological awareness; major cultural events; ecological theme messages; demographic-cultural characteristics